2020
DOI: 10.1016/j.jagp.2020.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Family Communication in Long-Term Care During a Pandemic: Lessons for Enhancing Emotional Experiences

Abstract: Highlights What is the primary question addressed by this study? The primary purpose of the study was to investigate which methods of communication during the COVID-19 pandemic were associated with more positive and less negative emotional experiences and perceptions of resident experiences of family members and friends of older adults in long-term care facilities in the United States. What is the main finding of this study? Using the ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 15 publications
0
55
1
4
Order By: Relevance
“…Data are beginning to emerge from studies documenting the experience for dementia caregivers during COVID‐19. For example, family caregivers who are able to engage in more direct phone and email contact with relatives in long‐term care residences indicated greater emotional well‐being for themselves and their relatives, whereas relying on residential care staff rather than family members to engage in communication resulted in lower perceived well‐being among family caregivers and their relatives 569 . Telephone interviews with family caregivers in rural Virginia following the governor's stay‐at‐home order found that those who were more concerned about the COVID‐19 pandemic and those who received less help from family and friends experienced greater feelings of emotional exhaustion and fatigue related to dementia care 570 …”
Section: Caregivingmentioning
confidence: 99%
“…Data are beginning to emerge from studies documenting the experience for dementia caregivers during COVID‐19. For example, family caregivers who are able to engage in more direct phone and email contact with relatives in long‐term care residences indicated greater emotional well‐being for themselves and their relatives, whereas relying on residential care staff rather than family members to engage in communication resulted in lower perceived well‐being among family caregivers and their relatives 569 . Telephone interviews with family caregivers in rural Virginia following the governor's stay‐at‐home order found that those who were more concerned about the COVID‐19 pandemic and those who received less help from family and friends experienced greater feelings of emotional exhaustion and fatigue related to dementia care 570 …”
Section: Caregivingmentioning
confidence: 99%
“…Insgesamt wurden 7224 Studienteilnehmende aus 14 Ländern berücksichtigt. Drei Studien schlossen Bewohner [ 3 , 12 , 28 ] und 4 Studien Angehörige ein [ 14 , 17 , 28 , 30 ], 10 Studien befragten Mitarbeitende [ 1 , 15 , 19 22 , 24 , 25 , 28 , 29 ]. Die Stichprobengröße reichte von 24 bis 1997 Teilnehmenden.…”
Section: Ergebnisseunclassified
“…Die Auswirkungen der Maßnahmen auf das psychische Befinden von Angehörigen werden in 5 Studien thematisiert [ 14 , 17 , 20 , 29 , 30 ], wobei die Gruppe in 3 Studien direkt befragt wurde. Dabei zeigte sich ein verringertes psychisches und emotionales Wohlbefinden.…”
Section: Ergebnisseunclassified
See 1 more Smart Citation
“…Few studies have directly asked targeted questions about perceived relationship quality during the pandemic (Biddle et al, 2020b;Bulow et al, 2020;Cooper et al, 2020), and even less about the use of technology-mediated communication (Monin et al, 2020). In a recent Australian study Biddle et al (2020b) asked their 3,249 respondents from the general public 'How has the quality of your relationships with other people/family members in your household changed since the spread of COVID-19?'.…”
Section: Research Investigating Social Relationships During Covid-19 mentioning
confidence: 99%